2021
DOI: 10.36941/ajis-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Visitor Management and its Impact on Visitor Experience and Satisfaction at Archaeological Sites in Jordan (Case Study: Jerash)

Abstract: This study aims to assess visitor management at the Jerash archaeological site in Jordan. It also sheds light on their approaches in guiding and managing visitors at the site, and to discover the effectiveness of adopting indirect approaches (soft strategies) by comparison to using direct approaches (hard strategies). This study examines the effects of visitor management practices on the level of experience quality for visitors, as well as on their satisfaction. The primary data has been obtained from various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Therefore, the results of this study indicate that visitor management via mobile application improves the satisfaction of residents living in strata properties. This finding supports the results of previous studies conducted by BK and Akshay (2021) and Qaddhat et al . (2021).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, the results of this study indicate that visitor management via mobile application improves the satisfaction of residents living in strata properties. This finding supports the results of previous studies conducted by BK and Akshay (2021) and Qaddhat et al . (2021).…”
Section: Resultssupporting
confidence: 94%
“…Similarly, the past studies have found security management system usage and residents' satisfaction to be positively correlated (Riratanaphong and Limjaroensuk, 2020; Sia et al ., 2018). Finally, visitor management system usage and resident satisfaction were also found to be positively associated (BK and Akshay, 2021; Qaddhat et al ., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%